Pengaruh Gaya Kepemimpinan, Kepuasan Kerja dan Komitmen Organisasi terhadap Kinerja Karyawan pada Dealer Honda MPM Motor Kupang - Nabuasa, Marchi Rocister; Niha, Simon Sia; Man, Stanis; Manafe, Henny A.; Adrianus, Jou Sewa (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of leadership style, job satisfaction, and organizational commitment simultaneously and partially on employee performance at the MPM Motor Kupang Honda Dealer. The techniques used in collecting data were questionnaires and interviews. The questionnaire used in this research was 36 questions consisting of 10 questions regarding employee performance, 10 questions about leadership style, 8 questions about job satisfaction and 8 questions about organizational commitment. Interviews are used as supporting data in this research, especially regarding employee conditions and comfort. The results of the research reveal that simultaneously and partially there is a significant and positive influence between the variables of leadership style, job satisfaction and organizational commitment on employee performance at the MPM Motor Kupang Honda Dealer.